MODEL PROMOSI KESEHATAN mu HAMIL GUNA MENINGKATKAN PERA WATAN KEHAMILAN DAN PERSALINAN PADA TENAGA KESEHATAN - , SHRIMARTI RUKMINI DEVY ([Yogyakarta] : FAKULTASKEDOKTERAN UNIVERSITAS GADJAH MADA YOGYAKA, 2013)
Background: variety of programs to improve maternal health, particularlypregnant mother, have been carried out by Ministryof Health, the Republic of Indonesia.However, to date the achievement of programs is not optimum. Preventive effort for the health of pregnant mother is one of the solutions to reduce the maternal mortality rate. Health promotion is one of the preventive efforts. This study designed an appropriate health promotion model in accordancewith local wisdom. Method: The study used a Quasi Experiment Nonequivalent Pre-test-Pos-test Control Group Design with quantitativeand qualitativeapproaches.It was conductedin Rapa Laok village and Tambak village in the work areas of Public Health Center 'Omben', Sampang Regency, Madura. The respondents of the study were pregnant motherswith the followingcriteria:pregnancy of trimesters 1 and 2 Data collection was done using 1) quantitative technique by structured interview